Analisis Pengaruh PDRB riil dan Inflasi terhadap Pengangguran di Kota Serang - Azizah, Siti Nijma; Jamaludin, Muhamad; Nariyah, Kamila (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The economic growth of each region is something that is highly hoped for by the community. Economic growth can be seen, among other things, from the increase in Real GDP and controlled inflation in an area. Apart from the increase in real GDP and inflation, of course every region has problems that cause economic growth to slow down, including unemployment. Therefore, the aim of this research is to understand the impact of GRDP and inflation on unemployment in Serang, which is the aim of this research. The data obtained comes from time series data originating from the Central Statistics Agency (BPS) database. Data for the period 2011–2022. The research results show that the real GRDP variable (X1) and the inflation variable (X2) have no effect on the poverty level (Y), while the inflation variable (T Test) has a negative effect on the poverty level. This shows that the results of the real GDP and inflation variables together contributed or contributed to changes in Y of 16.0% or 84%.